2020
DOI: 10.3389/fgene.2020.00795
|View full text |Cite
|
Sign up to set email alerts
|

Retro-Element Gypsy-163 Is Differentially Methylated in Reproductive Tissues of Apomictic and Sexual Plants of Cenchrus ciliaris

Abstract: Apomixis, an asexual mode of reproduction through seeds, has immense scope for crop improvement due to its ability to fix hybrid vigor. In C. ciliaris , a predominantly apomictically reproducing range grass, apomixis is genetically controlled by an apospory-specific-genomic-region (ASGR) which is enriched with retrotransposons. Earlier studies showed insertional polymorphisms of a few ASGR-specific retrotransposons between apomictic and sexual plants of C. ciliaris … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 67 publications
(79 reference statements)
0
13
0
Order By: Relevance
“…Moreover, a higher rate of CG methylation and a higher expression of retrotransposon transcripts was reported in sexual genotypes of E. curvula when compared to apomictic ones [45]. Otherwise, a recent work carried out in Cenchrus ciliaris showed that transcripts of Gy163, an LTR retrotransposon, are more expressed in the reproductive tissues of apomictic than of sexual plants, and this was correlated with reduced methylation level [98]. A recent study about the role of miRNA-mRNA interactions in apomixis development in E. curvula found that a transposon sequence was specifically repressed in the sexual genotype, most likely due to interactions with miRNAs [99].…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, a higher rate of CG methylation and a higher expression of retrotransposon transcripts was reported in sexual genotypes of E. curvula when compared to apomictic ones [45]. Otherwise, a recent work carried out in Cenchrus ciliaris showed that transcripts of Gy163, an LTR retrotransposon, are more expressed in the reproductive tissues of apomictic than of sexual plants, and this was correlated with reduced methylation level [98]. A recent study about the role of miRNA-mRNA interactions in apomixis development in E. curvula found that a transposon sequence was specifically repressed in the sexual genotype, most likely due to interactions with miRNAs [99].…”
Section: Discussionmentioning
confidence: 95%
“…The RE Ty3-gypsy was found to be differentially methylated/expressed in the reproductive tissues of apomictic and sexual plants. Hypomethylation was observed in CHH context in reproductive (aposporous initial and mature embryo sac) tissues of apomictic plants, which was directly correlated with the activity of the RE (Rathore et al, 2020). Thus, epigenetic regulation of seed development appears to be a common process in different plant species.…”
Section: Genome Imprinting and Heterosismentioning
confidence: 94%
“…In Arabidopsis as well as in other plants, the heterochromatic regions are enriched with methylcytosines, generally in the repetitive sequences and TEs. However, TEs and 5-mC are also found to be interspersed in the euchromatic regions (Zhang et al, 2006;Rathore et al, 2020). The dynamics of DNA base methylation depends on the reversibility of the processes, which also controls switching on/off the gene.…”
Section: Dynamics Of Dna Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…In plants, epigenetic mechanisms, such as DNA methylation, histone modifications, and small non-coding RNAs, are known to regulate gene expression changes in response to developmental and environmental cues (e.g. [28][29][30][31][32][33] ). Based on this evidence, epigenetic mechanisms are currently considered potentially important regulators of plants response to stress.…”
Section: Introductionmentioning
confidence: 99%